Magnetic surfaces of stellarator-mirror hybrid in the Uragan-2М torsatron - Lesnyakov, G.G.; Shapoval, A.N.; Gubarev, S.P.; Zolototrubova, M.S.; Opaleva, G.P.; Makhov, M.N.; Kotenko, V.G.; Moiseenko, V.E.; Voitsenya, V.S. (Вопросы атомной науки и техники, 2013)
This study was carried out in support of the possibility of a nuclear fusion neutron source based on the plasma trap with a stellarator-mirror hybrid magnetic system to control the subcritical, fast nuclear reactor. The experiments were performed in Uragan-2M device, the torsatron with additional toroidal magnetic field, to measure the magnetic surfaces when the stellarator-mirror magnetic system is created by switching off a single toroidal magnetic field coil. The experiments confirmed the existence of closed magnetic surfaces in such a combined system.